THE INFLUENCE OF GANDASIL D AND LIQUID WASTE ON THE GROWTH AND YIELD OF LETTUCE WITH THE HYDROPONICS OF WICK SYSTEM - Pitus, Agus tinus; Sc, Ir. Nurjani M.; SP.MP, Agus Hariyanti; S.P M.P, Dr. Tatang Abdurrahman (Jurnal Sains Mahasiswa Pertanian, 2021)
This study aims to obtain the best concentration combination of Gandasil D fertilizer and Tofu Liquid Waste for growth and yield on siomak lettuce with a hydroponic wick system technique. The study was conducted in one of the green houses of the Faculty of Agriculture, Tajungpura University, Pontianak, starting on October 31 until November 29, 2019. This study used a completely randomized design (CRD) with 5 treatments each treatment 5 times each, and each replica consisted of 6 plant samples so the total sample is 150 plants. The treatments a = 0.5 g / l Gandasil D + 60% Tofu Liquid Waste, b = 1 g / l Gandasil D + 50% Tofu Liquid Waste, c = 1.5 Gandasil D + 40% Tofu Liquid Waste, d = 2 g / l Gandasil D + 30% Tofu Liquid Waste, and e = 2.5 g / l Gandasil D + 20% Tofu Liquid Waste. The observable variables observed in this study were plant height (cm), number of leaves (sheet), plant fresh weight (g), plant dry weight (g), chlorophyll content (spad). the results of this study indicate that the treatment of Gandasil D fertilizer and Tofu Liquid Waste can make a difference to the growth and yield of the siomak lettuce in a hydroponic wick system.